1988
DOI: 10.1177/000348948809700107
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Ototoxicity by Glutathione Depletion

Abstract: The combination of 10 mg/kg ethacrynic acid (ETA) and 100 mg/kg kanamycin (KA) caused neither morphologic damage to the cochlea nor change in the auditory brain stem response of the chinchilla. However, after pretreatment with a single dose of buthionine sulfoximine (BSO; 800 mg/kg intraperitoneally) to reduce intracellular glutathione (gamma-glutamylcysteinylglycine; GSH) levels, the above single administration of ETA and KA resulted in complete deafness and severe morphologic damage. The kidney, which has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Oxidative stress has been implicated in the ototoxicity of several agents that potentiate NIHL, including aminoglycoside antibiotics (e.g., Garetz et al 1994;Hester et al 1998;Hoffman et al 1987Hoffman et al , 1988, the antineoplastic agent cisplatin Rybak et al 1995;Campbell et al 1996Campbell et al , 1999Gabaizadeh et al 1997), and carbon monoxide (Rao and Fechter 2000). Oxidative stress is also suspected to result from hydrogen cyanide treatment which also promotes NIHL (Fechter et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been implicated in the ototoxicity of several agents that potentiate NIHL, including aminoglycoside antibiotics (e.g., Garetz et al 1994;Hester et al 1998;Hoffman et al 1987Hoffman et al , 1988, the antineoplastic agent cisplatin Rybak et al 1995;Campbell et al 1996Campbell et al , 1999Gabaizadeh et al 1997), and carbon monoxide (Rao and Fechter 2000). Oxidative stress is also suspected to result from hydrogen cyanide treatment which also promotes NIHL (Fechter et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the metabolism of Ag to toxic compounds inactivated by glutathione in the ears and kidneys was proposed (10). Recently, two reports have demonstrated that a toxic metabolite had to be generated before Ag cytotoxicity to guinea pig cochlear hair cells could be obtained in vitro (5,11).…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete protection may be related to observations that many hydroxyl scavengers are only partially effective in inhibiting lipid peroxidation as they compete for OH in 'free solution' but do not cross the lipid membrane barriers to scavenge OH within the cells (for additional detail, see Halliwell and Gutteridge, 1998). Manipulation of endogenous GSH with the above agents also affects cisplatin-induced injury (Campbell et al, 1996;1999;Hu et al, 1999;Rybak et al, 2000;, and aminoglycoside ototoxicity (Hoffman et al, 1988;Garetz et al, 1994a;1994b;Lautermann and Schacht, 1996). Subsequent corroboration of the importance of endogenous antioxidants has come from genetically manipulated mice in which endogenous antioxidant protection was reduced via deletion of copper-zinc super oxide dismutase (Sod1) (Ohlemiller et al, 1999a;McFadden et al, 2001) or glutathione peroxidase (Gpx1) (Ohlemiller et al, 2000).…”
Section: Endogenous Antioxidant Defense Against Nihlmentioning
confidence: 99%